A Gala Performance tutu. (2nd January 2016) - Mida, Ingrid
Abstract : This research report considers a classical tutu belonging to the Ryerson Fashion Research Collection in Toronto that is now a shadow of its original conception—visibly faded, stained and torn, and crushed from more than 60 years in storage. Designed in 1953 for the corps de ballet of the National Ballet of Canada for the ballet Gala Performance, this paper will argue for retention of this tutu as material evidence of the history of a young ballet company that overcame significant obstacles in the early years of its existence and as a document of the ballet performance itself.